Consumer perception on sensory attributes of selected local Indonesian coffee - Isnidayu, Anandya Vanessa; Sukartiko, Anggoro Cahyo; Ainuri, Makhmudun (Penerbit Universiti Kebangsaan Malaysia, 2020)
The increase in coffee consumption for the last few years, especially for specialty coffee, becomes an opportunity to develop the local coffee market in Indonesia. In terms of developing local coffee, consumers’ sensory quality knowledge plays a vital role for coffee producer and marketer to increase sales. Taking this fact into account, the purpose of this study was to establish the quality of the sensory attributes of two selected local Indonesian coffee grown in Cianjur and Pangalengan, West Java. This study also aims to determine consumer perceptions of the attributes. Quality of the sensory attributes was evaluated by three certified panelists from the Indonesian Coffee and Cocoa Research Institute using cup testing method according to Specialty Coffee Association of America (SCAA) standard, while consumer perception was studied based on gap analysis between perceived importance and performance of the sensory attributes, assessed by 35 participants. Result revealed that the coffees had passed specialty grade and customer satisfaction, indicating the great potential for their market development. However, improvements in several sensory attributes such as flavour, aftertaste, and balance still need to be done.